2015
DOI: 10.1016/j.ssci.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Port safety evaluation from a captain’s perspective: The Korean experience

Abstract: There are many factors affecting navigational safety in ports, including weather, the characteristics of the channels and vessel types, etc. This paper aims to identify the factors influencing navigational safety in ports and to analyze the extent to which such factors affect the safety of ports from the perspective of ship captains through a real case study. A quantitative analysis is carried out using the data collected from 21 captains who have over 10 years experience in operating ships individually. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
1
40
1
Order By: Relevance
“…The weights vectors of performances and of KPIs under the performance and preferences vector of business processes for each KPI are calculated by using the method developed in Wu et al (2004). This can be denoted as the main difference between this paper and others Pak et al, 2015;Kaya and Kahraman, 2011;Hsu, 2012).…”
Section: Research Implicationsmentioning
confidence: 91%
See 4 more Smart Citations
“…The weights vectors of performances and of KPIs under the performance and preferences vector of business processes for each KPI are calculated by using the method developed in Wu et al (2004). This can be denoted as the main difference between this paper and others Pak et al, 2015;Kaya and Kahraman, 2011;Hsu, 2012).…”
Section: Research Implicationsmentioning
confidence: 91%
“…Different accidents could occur in ports, causing extensive loss of life, damage to vessels and cargo, serious water pollution and changes in biodiversity. The KPIs of seaport safety may be defined based on the literature (Pak et al, 2015;Trbojevic and Carr, 2000). Based on the literature review (Pak et al, 2015) and evidence data of Montenegro seaports, the following KPIs are identified as the most significant.…”
Section: Seaport Safetymentioning
confidence: 99%
See 3 more Smart Citations